Analisis Penerapan Sistem Informasi Akuntansi Penjualan Dalam Menunjang Efektivitas Pengendalian Internal Pada CV Agung Mandiri Motor - Elisabeth Sherly Noveli Simon; Maria Nona Dince; Emilianus Eo Kutu Goo (Jurnal Riset Akuntansi, 2023)
The formulation of the problem in this research is whether the implementation of the sales accounting information system is appropriate in supporting internal control at CV. Agung Mandiri Motor? This research aims to determine the application of the sales accounting information system in supporting the effectiveness of internal control at CV. Agung Mandiri Motor. This research was carried out at CV. Agung Mandiri Motor using qualitative methods. There are two sources of data in this research, namely primary data and secondary data. The data collection techniques used were documentation, interviews and observation. The data analysis technique used is by comparing the results of field findings with the cash and credit sales accounting information system theory at CV.Agung Mandiri Motor. The results of this research indicate that the sales accounting information system implemented by CV. Agung Mandiri Motor is not yet fully suitable to support the effectiveness of internal control.